Open knot‐tying skills: Resident skills assessed. Issue 5 (17th March 2013) - van, Pieter J.; Verdam, Mathilde G. E.; Huirne, Judith A.; Bonjer, H. Jaap; Meijerink, W. Jeroen; Scheele, Fedde
Abstract Aim Open knot‐tying and suturing skills are fundamental surgical skills, founding many alternative knot‐tying techniques. It is therefore mandatory for residents to possess adequate basic open knot‐tying skills. The aim of this study was to compare an objective assessment of open knot‐tying skills by residents to a resident's own estimation of his or her knot‐tying skills, before and after a knot‐tying course. Material and Methods A prospective observational cohort study was performed. At baseline level, after 1 training day in the Advanced Suturing Course (ASC) in the Netherlands and Belgium and after 6 weeks of autonomous practice (i.e. self‐practice), 99 residents' open knot‐tying skills were objectively evaluated using the Objective Structured Assessment of Technical Skills (OSATS). The resident's own confidence in these skills was also evaluated. Results The ASC substantially and significantly improved residents' knot‐tying skills according to the OSATS between baseline and post‐measurement. The observed improvement after 1 training day decreased after 6 weeks of autonomous practice. Self‐confidence increased directly after the training program and was maintained 6 weeks later. Residents having completed the first 3 years of residency displayed an overall greater self‐confidence than residents not having completed the first 3 years of residency, although the increase in self‐confidence was significantly larger in the latter after 6 weeks' autonomous training. Conclusion There is a divergence between residents' objectified open knot‐tying skills and self‐confidence in these skills. The ASC improved open knot‐tying skills according to the OSATS, however this improvement decreased after a 6‐week period of autonomous practice. Self‐confidence, in contrast, was maintained or increased. Further research is needed to correlate validated training programs with clinical outcomes and to determine whether residents' open knot‐tying skills and self‐confidence are retained beyond 1 year.